PETIK LAUT MUNCAR ECOTOURISM AND LITERARY TOURISM - Novi Anoegrajekti; Asrumi Asrumi; Sudartomo Macaryus; Dian Herdiati; Ifan Iskandar (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
Petik Laut Muncar is a village ritual for fishing communities in the Muncar Beach area. Bersih Desa represents gratitude for the fish-catch and safety that have been obtained during the past years by expecting for future catches and safety. This article aimed to explain marine rituals’ potential, namely Petik Laut as a basis for developing ecotourism and literary tourism. The research used the ethnographic method which began with providing library data by reading the library sources, such as books, articles, proceedings, and news about the potential of Petik Laut Muncar. The data obtained from the library sources were complemented by field data obtained through observation, participation, and in-depth interviews with selected informants, namely the head of the Muncar fishermen association, person-in-charge of Muncar fish market, businessmen for processing fish and other marine biotas, and local government in the Muncar’s Fishermen Beach area. Data analysis was carried out continuously since the data provision stage. Data interpretation is carried out semiotics by placing each event as a cultural sign that is interrelated as a whole. The potential for ecotourism on Muncar Fisherman Beach is mangrove forest, coral reef cultivation, and pearl shell cultivation. The potential for literary tourism at Muncar Fishermen Beach is the life story of Buyut Sayid Yusuf as a pioneer of the Muncar fishing village who was buried in Sembulungan Beach. The legend of Ulupang-pang Beach relating to the historical background of the struggle of the Using Banyuwangi people against the Dutch. and local government in the Muncar Fishermen Beach area. Data analysis was carried out continuously since the data provision stage. Data interpretation was carried out semiotically by placing each event as a cultural sign that was mutually related as a unity. The potential for ecotourism on Muncar’s fisherman was mangrove forest, coral reef, and pearl oyster cultivation. The potential for literary tourism at the Muncar Fishermen Beach area was the life story of Buyut Sayid Yusuf as a pioneer of Muncar fishing village who was buried in Sembulungan Beach. The legend of Ulupang-pang Beach related to the historical background of the struggle of the Using Banyuwangi people against the Dutch. and local government in the Muncar Fishermen Beach area.